SPATIAL AUTOCORRELATION UNTUK DETEKSI DATA KEWILAYAHAN PRODUK DOMESTIK REGIONAL BRUTO PROVINSI JAWA TENGAH - Muhammad Saifudin Nur; Abdul Karim (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Spatial Autocorrelationl is one of the method that can determined spatial characteristic in data variables. Sparial Autocorrelation is able to define whether there is spatial characteristic ineach variables at regression models. The purpose of this study is to map and Detecting the Spatial Autocorrelation  for Gross Regional Domestic Product (GDRP) data in Central Java province with appropriate spatial weighting. The data used is the GDRP data and the factors that affect the GDRPie labor, human capital, roads infrastructure in 2015. Based on the results, the spatial efect on GDRP data is significanly occurs. Keywords : Spatial Autocorrelation, Ordinary Least Square, GDRP